An investigation of cryptographically generated address (CGA)-based authentication for mobile IPv6 - Qadir, Sana; Siddiqi, Mohammad Umar (2014)
It is well known that the most promising approach to solving the problem of authentication in a mobile IPv6 network is to use CGA-based authentication. The only drawback is that CGA algorithms can be computationally expensive. This study analyses the performance of the CGA generation algorithm and proposes changes to impose a minimal computational security while maintaining reasonable performance. This study also compares the use of Rivest Shamir Adleman (RSA) signatures with the Merkle Signature Scheme (MSS) for generating CGA Signatures. It finds that using MSS significantly improves the key generation time. However, more work needs to be done to improve both the CGA generation algorithm and MSS in order to make CGA-based authentication an attractive option in MIPv6 setups.